THE USE OF ANIMATED VIDEO TO AID FIRST GRADE STUDENTS OF STARLIGHT TUITION IN MASTERING â€œNUMBERâ€ FOR THE ACADEMIC YEAR 2021-2022 - Cameyylia Nur Fatmasari; Dina Kartikawati (Universitas Labuhanbatu, 2022)
Most of the 1st grade students of Starlight Tuition 1 Tulungagung have difficulty in mastering English material, especially numbers. Therefore, researchers conducted research using the Video Based Learning method to facilitate mastery of the material. This study aims to describe how animated videos can improve the ability of first graders of Starlight Tuition in mastering numbers. This study involved 32 subjects from grade 1 students of Starlight Tutition 1 Tulungagung. Like other Classroom Action Research, this research also goes through 4 stages those are planning, action, observation, and reflection. During this research, the researcher also acts as the teacher. This research stopped in cycle 1 only because the students' test results were sufficient and met the criteria of success. After doing research and testing, the post test results greatly improved. In the pre-test, the total score of students was 2210 and the number of students who took the test was 32. The mean of students was 69.06. 13 children did not meet the criteria for success. But in the post-test, the total score of students was 2990 and the number of students was 32 students. The mean of students was 93.44. Only 4 children met the criteria for failure.Keywords: numbers, video-based learning, classroom action research